Habitat filtering by landscape and local forest composition in native and exotic New Zealand birds. Issue 1 (1st January 2014) - Barnagaud, Jean-Yves; Barbaro, Luc; Papaïx, Julien; Deconchat, Marc; Brockerhoff, Eckehard G.
Abstract : Untangling the relative influences of environmental filtering and biotic interactions on species coexistence at various spatial scales is a long‐held issue in community ecology. Separating these processes is especially important to understand the influences of introduced exotic species on the composition of native communities. For this aim, we investigated coexistence patterns in New Zealand exotic and native birds along multiple‐scale habitat gradients. We built a Bayesian hierarchical model, contrasting the abundance variations of 10 native and 11 exotic species in 501 point counts spread along landscape and local‐scale gradients of forest structure and composition. Although native and exotic species both occurred in a wide range of habitats, they were separated by landscape‐level variables. Exotic species were most abundant in exotic conifer plantations embedded in farmland matrices, while native birds predominated in areas dominated by continuous native forest. In exotic plantation forests, and to a lesser extent in native forests, locally co‐occurring exotic and native species were segregated along a gradient of vegetation height. These results support the prediction that exotic and native bird species are segregated along gradients related to anthropogenic disturbance and habitat availability. In addition, native and exotic species overlapped little in a multivariate functional space based on 10 life history traits associated with habitat selection. Hence, habitat segregation patterns were probably mediated more by environmental filtering processes than by competition at landscape and local scales.